Encrypted image-based data hiding technique using elliptic curve ElGamal cryptography. (2018) - Jayanthi, R.; Singh, K. John
Most of the data hiding techniques used RSA-basedencryption algorithms for encrypting the images and the messages. However, the security provided by elliptic key cryptography is higher with a lower size key than the RSA algorithm. Therefore, a new image encryption scheme which can be reversed during decryption is proposed in this paper which uses an elliptic curve key-basedElGamal encryption scheme for effective data hiding in images. Moreover, it uses the difference scheme available in the existing work for data hiding of images. From the experiments conducted in this work, it is proved that the proposed scheme is more efficient with respect to security and it reduces the computation complexity when it is compared with other related schemes.